A Conceptual Framework for Analysing Inter-municipal Cooperation on the Environment. Issue 6 (2nd June 2016) - Lintz, Gerd
Abstract : Lintz G. A conceptual framework for analysing inter-municipal cooperation on the environment, Regional Studies . While there is a wealth of literature on cooperation between cities, local environmental policy-making and regional sustainable development, voluntary inter-municipal collaboration between neighbouring municipalities on environmental issues seems to have been neglected. This paper presents a conceptual framework for analysing the factors that influence such cooperation, drawing on actor-centred and discursive institutionalism and explicitly considering the aspects knowledge, values and power. It integrates substantive and interaction-oriented analysis of sectoral and territorial coordination in a two-level governance setting, examining intra- and inter-municipal as well as global environmental effects. The study thus provides a systematic basis for further theoretical and empirical research. Abstract :